Novel and extendable genotyping system for human respiratory syncytial virus based on whole‐genome sequence analysis. Issue 3 (10th December 2021) - Chen, Jiani; Qiu, Xueting; Avadhanula, Vasanthi; Shepard, Samuel S.; Kim, Do‐Kyun; Hixson, James; Piedra, Pedro A.; Bahl, Justin
Abstract: Background: Human respiratory syncytial virus (RSV) is one of the leading causes of respiratory infections, especially in infants and young children. Previous RSV sequencing studies have primarily focused on partial sequencing of G gene (200–300 nucleotides) for genotype characterization or diagnostics. However, the genotype assignment with G gene has not recapitulated the phylogenetic signal of other genes, and there is no consensus on RSV genotype definition. Methods: We conducted maximum likelihood phylogenetic analysis with 10 RSV individual genes and whole‐genome sequence (WGS) that are published in GenBank. RSV genotypes were determined by using phylogenetic analysis and pair‐wise node distances. Results: In this study, we first statistically examined the phylogenetic incongruence, rate variation for each RSV gene sequence and WGS. We then proposed a new RSV genotyping system based on a comparative analysis of WGS and the temporal distribution of strains. We also provide an RSV classification tool to perform RSV genotype assignment and a publicly accessible up‐to‐date instance of Nextstrain where the phylogenetic relationship of all genotypes can be explored. Conclusions: This revised RSV genotyping system will provide important information for disease surveillance, epidemiology, and vaccine development.